Annual reports on NMR spectroscopy. - Webb, G. A. (Graham Alan), 1935- (Annual reports on NMR spectroscopy, 2020)
Annual Reports on NMR Spectroscopy, Volume 99, provides an in-depth accounting of progress in nuclear magnetic resonance (NMR) spectroscopy and its many applications. Specific chapters in this new release include Recent Developments in the accurate measurement of NMR Transverse Relaxation Times, NMR Studies of the Binding and Dynamics of Ionic Liquids with Proteins, Recent Developments in 1HNMR Relaxometry, Solid State 19F NMR Studies of Oriented Peptides, and Applications of Nuclides other than 1H and 13C in Solid State NMR Studies of Pharmaceuticals. --